Impact of Nitrogen Levels and Planting Density on the Growth and Yield of Okra (Abelmoschus esculentus L. Moench) - Funda Yoldaş; Şafak Ceylan; İbrahim Duman; Ömer Lütfü Elmacı; Eftal Düzyaman (Turkish Journal of Agriculture: Food Science and Technology)
The study was carried out to the effects of different plant densities and nitrogen levels on okra yield and plant development. Field trials were conducted in two locations, the training fields of the Ege University, Ödemiş Research and Training area, and Ege University Faculty of Agriculture, Menemen Research and Training Farm. The field layout was a split-plot design with 3 replicates, where main plots consisted of nitrogen applications and sub-plots of plant densities. Fertilizer was applied in the form of Triple Superphosphate, Potassium Sulfate, Urea and Ammonium Nitrate. Five different nitrogen levels (F1: 0, F2: 40, F3: 80; F4: 120 and F5: 160 kg N ha-1) and two different rows spacing (PD1: 15 cm×70 cm and PD2: 25 cm×70 cm) have been tested. Yield and yield components, plant height at flowering, height of the first fruits, the number of leaves, the number of branches, the number of days from sowing to first flowering, the number of days from sowing to first harvest, plant height, foliation status, total yield, yield of plant, average fruit weight, fruit length, fruit diameter have been noted in the field experiments. Total yield ranged from 5923.8 to 12888.9 kg ha-1 at the Ödemiş location, while it was 3363.3-5009.2 kg ha-1 at the Menemen location. In conclusion, the highest yield is taken from F2 in both plant densities in Ödemiş. In Menemen, the highest yield is taken from the dose of F3 (80 kg Nha-1) and F4 (120 kg Nha-1).